Phosgene-free synthesis of N-methyl-N′,N′-diphenylurea - E.P. van Geest; J.J.M.H. van den Elshout; J.F. Zevenbergen; A.E.D.M. van der Heijden (Current Research in Green and Sustainable Chemistry, 2022)
Akardite II (AK-II, N-methyl-N′,N′-diphenylurea) is a well-known stabilizer for nitrocellulose (NC) propellants as it scavenges NOx. Currently, AK-II is produced using phosgene, a highly toxic gas. An alternative, two-step synthesis route is presented here that does not rely on phosgene. First, symmetrical organic carbonates (R2CO3, with R ​= ​Me, Et, or Ph) and diphenylamine react to form their corresponding carbamates in good yields for R ​= ​Me and Et (80% and 57%) and low yield for R ​= ​Ph (9%), catalyzed by 3-methyl-1-butylimidazolium chloride ([BMIM]Cl). The carbamate species are suggested to be formed in an equilibrium reaction. Evaporation of the alcohol side products pushes the equilibrium to the carbamate product. The second step converts the diphenyl carbamates into the targeted compound by treatment with (mono)methylamine (MMA), with reversed yield trend (4% for R ​= ​Me and Et, 81% for R ​= ​Ph). For the alkyl carbamates, the formation of AK-II appears to run in parallel with an MMA-alkylation reaction, which severely lowers the product yield. Overall, the synthesis of AK-II via the carbamate route is feasible, yet the carbonate side groups should be chosen carefully to obtain a high overall yield.